2021
DOI: 10.15585/mmwr.mm7035e5
|View full text |Cite
|
Sign up to set email alerts
|

Association Between COVID-19 and Myocarditis Using Hospital-Based Administrative Data — United States, March 2020–January 2021

Abstract: On August 31, 2021, this report was posted as an MMWR Early Release on the MMWR website (https://www.cdc.gov/mmwr).Viral infections are a common cause of myocarditis, an inflammation of the heart muscle (myocardium) that can result in hospitalization, heart failure, and sudden death (1). Emerging data suggest an association between COVID-19 and myocarditis (2-5). CDC assessed this association using a large, U.S. hospital-based administrative database of health care encounters from >900 hospitals. Myocarditis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
219
2
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 249 publications
(243 citation statements)
references
References 10 publications
17
219
2
5
Order By: Relevance
“…Patients with myocarditis were more commonly male (59.3 versus 41.7%). Despite the limitations, the observed myocardial lesions in our cohort may still be concordant with other studies ( Boehmer et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…Patients with myocarditis were more commonly male (59.3 versus 41.7%). Despite the limitations, the observed myocardial lesions in our cohort may still be concordant with other studies ( Boehmer et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…36 Another study reported an adjusted risk ratio for myocarditis from patients with COVID-19 compared with patients without COVID-19 of 36.8 in children less than 16 years of age and 7.4 in adolescents 16-24 years of age. 37 A third study reported an 8.2-fold increase in myocarditis admissions during the pandemic, but no cases among the 1371 children and adolescents less than 18 years of age. 38 Information on the long-term outcome of myocarditis resulting from SARS-CoV-2 infection (e.g., progression to fibrosis) is currently lacking.…”
Section: Potential Benefits Of Vaccinating Children Protection Against Covid-19mentioning
confidence: 96%
“… 11 As of September 1 2021, the Centers for Disease Control and Prevention writes that the risk of myocarditis is far higher after COVID-19 infection as opposed to the mRNA virus. 12 Based on a study that identified 1.5 million inpatient records with COVID-19, myocarditis was uncommon among patients with or without COVID-19, however, there was a relatively higher risk in the 50 to 75 and over age groups. 12 The under 16 age group could be more prone due to the related multisystem inflammatory syndromes.…”
Section: Introductionmentioning
confidence: 99%
“… 12 Based on a study that identified 1.5 million inpatient records with COVID-19, myocarditis was uncommon among patients with or without COVID-19, however, there was a relatively higher risk in the 50 to 75 and over age groups. 12 The under 16 age group could be more prone due to the related multisystem inflammatory syndromes. 12 The paper also noted an 18-fold higher chance of developing myocarditis due to COVID-19.…”
Section: Introductionmentioning
confidence: 99%